METHODS FOR DETERMINING THE NEED TO USE THE METRO IN TRANSPORT SYSTEMS OF BIG CITIES BY MATHEMATICAL SIMULATION - Ikromov Akmaljon Gofurjonovich (Journals Park Publishing, 2023)
This paper provides the results of the experiment carried out on the transport system of Krasnodar for three settlement periods - 2007, 2017, 2022 years. The experiment was carried out on using the passenger flow model based on the iterative process of changing passenger traffic and speeds in a conditional transport network. The model assumes determining the need for high-speed public transport, in particular, the subway and designing of potential high-speed routes in accordance with passenger flow.
Keywords: city’s transport system, transport management, public transport, modeling, transport flow, passenger transport correspondence, passenger flow.